Perceptions, experiences, barriers, facilitators, learning outcomes, and modes of assessment of digital clinical placements for pre-registration physiotherapy students internationally: a systematic review protocol - Justin McConnell; Alison Rushton; Tim Noblet; Verity Pacey; Jai Mistry; Jeremy Lai; Daphne Nguyen; Samantha Doralp (PLoS ONE, 2025)
Introduction The shift to digital clinical placements for physiotherapy education due to COVID-19 prompts a need for evaluation of current evidence. Existing studies highlight benefits of digital technology in clinical placements, but lack of a systematic review focused on pre-registration physiotherapy students is a key gap. This systematic review will address this gap by synthesizing the evidence for digital clinical placements for pre-registration physiotherapy students internationally. Methods and analysis This systematic review is designed using the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) statement and Cochrane Handbook – it is registered on PROSPERO (CRD42024571696). Search terms will be adapted to each database, including EMBASE, MEDLINE, PROSPERO, ERIC, and CINAHL. Key journals, forward citation tracking, references of included studies, and professional organization websites will also be searched. The search will include studies published since database inception to 31/05/24. There will be no limit to study design or language. Studies that report on perceptions, experiences, barriers, facilitators, learning outcomes, and modes of assessment of digital clinical placements for pre-registration physiotherapy students will be included. Meta-aggregation will be used to synthesize themes from findings which enables the generation of themes without the need to re-interpret data and the loss of study specific context. Ethics and dissemination Ethics approval is not required. The results of this study will be written up for publication in relevant peer-reviewed scientific journals and contribute to a developing area of research. Results will also be presented at national or international conferences, events for the physiotherapy profession, or education events.